Green antifungal waterborne coatings based on essential oil microcapsules - Revuelta, Mariana Valeria (2020)
There is a great concern about the indoor microbial colonization especially in places that should have high standards of environmental hygiene. Besides, due it shortened the useful life of the coating by discoloration and degradation. Currently this is a problem that must be solved in an innovative and eco-friendly way. In this sense, the aim of the work was to develop a green waterborne paint formulated with microcapsules containing es- sentials oil as biocide agent. This novel hygienic coating would be applied as to protect indoor surfaces from fungi. The microcapsules were synthesized by interfacial polymerization. Melamine-formaldehyde (MF) resin was used for the microcapsule shell wall, and Lavandin and Tea Tree essential oils (EOs) as core materials. The synthesized microcapsules were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy and particle size analysis. Preparation of acrylic waterborne paint was performed and the micro- capsules MF-EOs were dispersed into the original paint just before application on commercial gypsum boards. The stability of the MF-EOs in the paint was successfully achieved. Two control paints were used, one containing EOs in free form and other without biocide. The effectiveness of the microcapsules into paint film against spore suspension of Aspergillus fumigatus was evaluated by seeding the fungus on the painted surface. The fungal growth was evaluated according to ASTM D5590 standard specification. The score obtained from MF-Lavandin paint indicates just a trace growth onto the painted surface (<10 %). On the control and MF-Tea tree paints the growth was 70 %. The MF-Lavandin showed a high inhibition activity against fungal in the dry paint film compared with the one containing free form EOs paint.